On ethnofagic neo-indigenism:The Prodepine experience or the limits of Neoliberal multiculturalism - Bretón, Víctor (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2007)
This text explores some of the new methods of intervention that have been tested in rural areas since the consolidation of the Post-Washington Consensus. Particularly, it seeks to evaluate the definition of the concept, social capital, by its application in different developmental agencies. The specific case of analysis in this article is of the Proyecto de Desarrollo de los Pueblos Indígenas y Ne g ros del Ecuador (PRODEPINE, Ec u a d o r’s Indigenous and Afro - Ecuadorian Peoples Development Project). This has been a pioneering initiative in the American continent, and draws on the importance of strong organisation as the main strategy to attack the challenges faced by the new rural class. The idea is not so much to assess the analytical virtues and limits of the social capital concept, but to question the ways in which it has been understood and materialised by institutions, especially international ones, like the World Bank. At the end of the article, the results of the analysis studied in the Andes of Ecuador will show the effects of neoliberalism on the indigenous movement in Ecuador.